\(\frac{5.5.5}{\frac{5.5.5}{5}}+5.5\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

15 tháng 11 2016

 \(\frac{2^5.7+2^5.59}{2^5.5^2-2^5.3}\)

=\(\frac{\left(2^5\right).\left(7+59\right)}{\left(2^5\right).\left(5^2-3\right)}\)

=\(\frac{7+59}{5^2-3}\)

=\(\frac{64}{22}\)

=\(\frac{32}{11}\)

17 tháng 7 2015

85.(8 + 5) = 85.13 =1105

8.8.8 + 5.5.5 = 512 + 125 = 637 

=> 85.(5+8)  > 8.8.8 + 5.5.5 

8 tháng 2 2019

\(3+\frac{2}{5}-\frac{3}{4}\times\frac{4}{5}\)

\(=3+\frac{2}{5}+\frac{3}{5}\)

\(=3+1\)

\(=4\)

22 tháng 10 2017

a, 6/9+5/7+1/3=2/3+5/7+1/3=5/7+1=12/7

b, 17/7+6/5-20/14=17/7+6/5-10/7=6/5+1=11/5

c,2/5x1/4+3/4x2/5=2/5x(1/4+3/4)=2/5x1=2/5

d, 6/11:4/6+5/11:2/3=6/11:2/3+5/11:2/3=(6/11+5/11):2/3=3/2

nha

28 tháng 4 2019

\(\left(\frac{1}{2}+\frac{3}{5}-\frac{2}{5}\right):\frac{3}{5}\)

\(=\frac{7}{10}:\frac{3}{5}\)

\(=\frac{7}{6}\)

28 tháng 4 2019

\(\left(\frac{1}{2}+\frac{3}{5}-\frac{2}{5}\right):\frac{3}{5}\)

\(=\left(\frac{5}{10}+\frac{6}{10}-\frac{4}{10}\right):\frac{3}{5}\)

\(=\left(\frac{5+6-4}{10}\right):\frac{3}{5}\)

\(=\frac{7}{10}:\frac{3}{5}\)

\(=\frac{7}{10}\times\frac{5}{3}\)

\(=\frac{7}{6}=1\frac{1}{6}\)

8 tháng 6 2018

a) \(\frac{2}{11x16}+\frac{2}{16x21}+...+\frac{2}{61x66}\)

\(=\frac{2}{5}x\left(\frac{1}{11}-\frac{1}{16}+\frac{1}{16}-\frac{1}{21}+...+\frac{1}{61}-\frac{1}{66}\right)\)

\(=\frac{2}{5}x\left(\frac{1}{11}-\frac{1}{66}\right)\)

\(=\frac{2}{5}x\frac{5}{66}\)

\(=\frac{1}{33}\)

b) \(\frac{2}{5x7}+\frac{4}{7x11}+\frac{3}{11x14}+\frac{4}{14x18}+\frac{5}{18x23}+\frac{7}{23x30}\)

\(=\frac{1}{5}-\frac{1}{7}+\frac{1}{7}-\frac{1}{11}+\frac{1}{11}-\frac{1}{14}+\frac{1}{14}-\frac{1}{18}+\frac{1}{18}-\frac{1}{23}+\frac{1}{23}-\frac{1}{30}\)

\(=\frac{1}{5}-\frac{1}{30}\)

\(=\frac{1}{6}\)

8 tháng 6 2018

a, \(\frac{2}{11\times16}+\frac{2}{16\times21}+...+\frac{2}{61\times66}\)

\(=\frac{2}{5}\times\left(\frac{5}{11\times16}+...+\frac{5}{61\times66}\right)\)

\(=\frac{2}{5}\times\left(\frac{1}{11}-\frac{1}{16}+...+\frac{1}{61}-\frac{1}{66}\right)\)

\(=\frac{2}{5}\times\left(\frac{1}{11}-\frac{1}{66}\right)\)

\(=\frac{2}{5}\times\frac{5}{66}\)

\(=\frac{1}{33}\)

Vậy giá trị của biểu thức trên là : \(\frac{1}{33}\)

b,\(\frac{2}{5\times7}+\frac{4}{7\times11}+\frac{3}{11\times14}+\frac{4}{14\times18}+\frac{5}{18\times23}\)

\(=\frac{1}{5}-\frac{1}{7}+\frac{1}{7}-\frac{1}{11}+\frac{1}{11}-\frac{1}{14}+\frac{1}{14}-\frac{1}{18}+\frac{1}{18}-\frac{1}{23}\)

\(=\frac{1}{5}-\frac{1}{23}\)

\(=\frac{18}{115}\)

Vậy giá trị của biểu thức trên là \(\frac{18}{115}\)